Strategi Kepemimpinan Kepala Sekolah dalam Branding Sekolah untuk Meningkatkan Trust Masyarakat: Studi di SD YPI Darussalam Cerme - Mas'ud Mas'ud; Ahmad Thohirin; A. Faizin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The principal, as an educational leader, plays a key role in building public trust. In today's era of global competition and educational decentralization, schools are required to demonstrate their existence and competitiveness. This is the case at SD YPI Darussalam Cerme, a private school competing with public schools. This study aims to describe the principal's strategy in building public trust at SD YPI Darussalam. Data collection techniques were carried out through in-depth interviews, participant observation, and documentation studies. The results show that the principal implemented transformational leadership strategies, strengthening institutional values, stakeholder involvement, and effective media use. This strategy successfully increased public trust and strengthened the school's position as a quality and competitive educational institution. These findings help deepen the understanding of leadership in education and provide concrete evidence supporting the principal's leadership strategy model.